Myocardial fatty acid utilisation during exercise induced ischemia in patients with coronary artery disease - Virtanen, K. S.; Nikkinen, P.; Lindroth, L.; Kuikka, J. T. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: Reversible or irreversible myocardial damage due to ischemia correlates with altered membrane functions of the cells. To compare myocardial free fatty acid (FFA) metabolism and flow during exercise induced ischemia we studied ten patients with coronary artery disease but without previous myocardial infarction. Methods: A series of post-exercise single-photon emission computed tomography (SPECT) measurements was performed after injection of 123I labelled heptadecanoic acid (HDA). Myocardial perfusion was estimated from the separately performed exercise-redistribution thallium study. Fatty acid metabolic rate, thallium uptake and washout were calculated for anterior, lateral, posterior and septal segments. Results: The more reduced post-exercise FFA metabolic rate (–63 ±18%, mean ±1 SD) compared to flow (–36 ±16%) was related to the severity of myocardial ischemia and wall motion abnormalities. Conclusion: In this small group of patients, the reduced post-exercise FFA metabolic rate tentatively suggests a parsimonious workload of the exercising myocardium by reducing oxygen consumption in patients with coronary artery disease.
Keywords: Coronary artery disease; fatty acids; ischemia